Compósitos híbridos com fibras de bambu (Bambusa vulgaris) e lama vermelha: efeito do tratamento químico na resistência à tração dos compósitos - FARIAS, Dorivane Cohen (2019)
The vast area of science and engineering of materials feature a wide variety of applications, including the production of polymeric composites embedded with a wide variety of materials from natural sources, of easy accessibility, great abundance and considered sustainable. In this work, were produced polymer matrix composites embedded with red mud and hybrid composites with red mud and bamboo fibres chemically treated and untreated, for mechanical analysis of traction and fractográfica. The polymeric matrix used was the isoftálica unsaturated polyester resin along with cobalt Accelerator (1.5 % v/v) and catalyst (1 % v/v). Bamboo culms were collected on Campus Professional I (a) of the Federal University of Pará. The fibres were drawn by hand, cut in 15 mm lengths and subjected to chemical treatments in alkaline solution with 5 % sodium hydroxide (NaOH). The red mud from the company Hydro Alunorte, was manually sifted in size 100 mesh sieve and characterized by x-ray diffraction-X (DRX). The composites manufacturing process followed by the manual lamination (hay layup). The proportions of red mud included in composites were of 10 %, 20 %, 30 % and 40 %. For the hybrid composites were inserted the following proportions: 3 %/10 %, 3% /20 %, 3 %/30 % and 3 %/40 % (fibre/Residue). Being made 10 (ten) specimens for each series manufactured. The composites produced were analysed as your tensile strength according to ASTM D3039. Fractográficas analyses were performed by scanning electron microscopy (SEM). Best result for composites with incorporation of residue had the proportion 20 % with a ceiling of 36.63 MPa. For hybrid composites with non-treated fibers insertion and residue, better tensile strength limit was 36.25 MPa for the proportion of 3 % and 10 % of waste fibres, hybrid composites with fiber and residue insertion, the best result fo (I) to 3 %/10 % proportion with a 35.30 MPa boundary. The fractografia held in the fracture morphologies of composites showed mechanisms such as: cracks in the array, and desfibrilamento fibre separation, broken fibers and fibers torn out (pull-out).